"We lost all we had in a second": coping with grief and loss after a natural disaster. Issue 1 (7th March 2013) - Ekanayake, Samanthika; Prince, Martin; Sumathipala, Athula; Siribaddana, Sisira; Morgan, Craig
<x xml:space="preserve">Abstract</x> Natural disasters cause immense suffering among affected communities. Most occur in developing countries, which have fewer resources to respond to the resulting traumas and difficulties. As a consequence, most survivors have to rely on their own coping resources and draw from what support remains within family, social networks and the wider community to manage and deal with their losses and consequent emotional distress. Taking the 2004 Asian tsunami as an example, this article reports findings from a qualitative study designed to investigate how survivors responded in Sri Lanka, and the range of coping strategies adopted and resources mobilized. In‐depth interviews were conducted with 38 survivors purposively sampled from the Matara district of southern Sri Lanka. Survivors' accounts emphasized the importance of extended supportive networks, religious faith and practices, and cultural traditions in facilitating recovery and sustaining emotional well‐being. Government and external aid responses that promoted these, through contributing to the re‐establishment of social, cultural, and economic life, were particularly valued by participants. Recourse to professional mental health care and Western psychological interventions was limited and survivors preferred to seek help from traditional and religious healers. Our findings tentatively suggest that long‐term mental health following disaster may, in the first instance, be promoted by supporting the re‐establishment of those naturally occurring resources through which communities traditionally respond to suffering.